(untitled) (Research, Society and Development, 2023)
Squamous cell carcinoma is a malignant neoplasm that is characterized by invasiveness and a low rate of metastases. It is commonly observed in fair-skinned cats with low hair density and is characterized by edema, ulceration with the presence of granulation tissue and hematic crusts. The diagnosis may require extensive knowledge from the veterinarian, who needs to carry out a differential investigation for other diseases. There are some therapeutic protocols, the effectiveness of which still depends on the extent and evolution of the lesions. In several cases, controlling exposure to perpetuating factors appears to slow disease progression. The objective of the present study was to report a case of squamous cell carcinoma in a feline patient, female, with no racial definition and approximately three years old, treated at a private veterinary dermatology service in the east zone of the city of São Paulo. The patient had ulceration in the cephalic region, with the presence of serosanguinous secretion, hematic crusts, with areas of tissue necrosis and granulation tissue on the lateral face of the left ear and nasal plane. The presumptive diagnosis was made by cytological examination and was confirmed by anatomopathology. The following procedures were adopted: surgery to remove the left auricle and instituted Imiquimod. After 30 days, the patient presented total remission of the lesions, without any recurrence so far. The tutor was instructed to keep the patient under surveillance and that she was not exposed to solar radiation.